2013
DOI: 10.1021/ja308993g
|View full text |Cite
|
Sign up to set email alerts
|

Oxo-Functionalization and Reduction of the Uranyl Ion through Lanthanide-Element Bond Homolysis: Synthetic, Structural, and Bonding Analysis of a Series of Singly Reduced Uranyl–Rare Earth 5f1-4fn Complexes

Abstract: The heterobimetallic complexes [{UO2Ln(py)2(L)}2], combining a singly reduced uranyl cation and a rare-earth trication in a binucleating polypyrrole Schiff-base macrocycle (Pacman) and bridged through a uranyl oxo-group, have been prepared for Ln = Sc, Y, Ce, Sm, Eu, Gd, Dy, Er, Yb, and Lu. These compounds are formed by the single-electron reduction of the Pacman uranyl complex [UO2(py)(H2L)] by the rare-earth complexes Ln(III)(A)3 (A = N(SiMe3)2, OC6H3Bu(t)2-2,6) via homolysis of a Ln-A bond. The complexes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 83 publications
3
75
0
1
Order By: Relevance
“…68, 72 Moreover, examples of unambiguous magnetic coupling between uranium ions in molecular systems remain very limited41, 7377 although such interactions are at the origins of the single‐molecule magnet behavior recently reported for few multinuclear U III and U V complexes 19. 78, 79…”
Section: Resultsmentioning
confidence: 99%
“…68, 72 Moreover, examples of unambiguous magnetic coupling between uranium ions in molecular systems remain very limited41, 7377 although such interactions are at the origins of the single‐molecule magnet behavior recently reported for few multinuclear U III and U V complexes 19. 78, 79…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7] For example, Arnold and co-workers demonstrated that sequential reaction of U VI O 2 (THF)(H 2 L) (L = polypyrrolic macrocycle) with KN(SiMe 3 ) 2 and FeI 2 resulted in formation of the U(V) silyloxide, [U V O(OSiMe 3 )(THF)Fe 2 I 2 L]. 7 Similarly, our research group has demonstrated that reaction of U VI O 2 ( Ar acnac) 2 ( Ar acnac = ArNC(Ph)CHC(Ph)O, Ar = 3,5-t Bu 2 C 6 H 3 ), 8 with a mixture of B(C 6 F 5 ) 3 and HSiR 3 (R = Ph, Et), 9,10 or with Ph 3 SiOTf alone, 11 results in formation of the reductive silylation products, U V (OSiR 3 )(OB{C 6 11 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The slow progress in the field is in part due to the relative smallness of the actinide scientific community, and to the fact that only a handful of laboratories are equipped to handle transuranic elements, so that most of the reported work concerns uranium complexes only. SMM behaviour has actually been observed in several monometallic U III [13] and U V [14] complexes and in heterometallic coordination compounds containing U V and either Mn II or Dy III cations [15][16][17].…”
Section: A Survey Of the Existing Transuranic Single Molecule Magnetsmentioning
confidence: 82%